2021
DOI: 10.1155/2021/4475968
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Low‐Dose Alcohol against Acute Stress‐Induced Renal Injury in Rats: Involvement of CYP4A/20‐HETE and LTB4/BLT1 Pathways

Abstract: Low-dose alcohol possesses multiple bioactivities. Accordingly, we investigated the protective effect and related molecular mechanism of low-dose alcohol against acute stress- (AS-) induced renal injury. Herein, exhaustive swimming for 15 min combined with restraint stress for 3 h was performed to establish a rat acute stress model, which was verified by an open field test. Evaluation of renal function (blood creatinine and urea nitrogen), urine test (urine leukocyte esterase and urine occult blood), renal his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 66 publications
(68 reference statements)
3
0
0
Order By: Relevance
“…Longer distances, more rearing times, and higher crossing times indicate higher levels of exploratory behavior. 33 The rats after chronic restraint stress show a less total distance, crossing number, and rearing number in OFT and higher CORT content, which is consistent with preceding studies on the effects of chronic stress. 34 Notably, the chronic stress model is successfully established.…”
Section: ■ Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Longer distances, more rearing times, and higher crossing times indicate higher levels of exploratory behavior. 33 The rats after chronic restraint stress show a less total distance, crossing number, and rearing number in OFT and higher CORT content, which is consistent with preceding studies on the effects of chronic stress. 34 Notably, the chronic stress model is successfully established.…”
Section: ■ Discussionsupporting
confidence: 91%
“…The number of crossing, rearing number, and the total distance measure the explored ability of experimental animals in new environments. Longer distances, more rearing times, and higher crossing times indicate higher levels of exploratory behavior . The rats after chronic restraint stress show a less total distance, crossing number, and rearing number in OFT and higher CORT content, which is consistent with preceding studies on the effects of chronic stress .…”
Section: Discussionsupporting
confidence: 90%
“…Interestingly, it was found that a chronic but small amount of alcohol consumption increases the SOD levels [47]; in this study, we found similar results as our dose (80% average 1mL/250 of rat) was even smaller than the one used in the study as mentioned above (0.05g/kg). SOD levels in GC and CAP groups did not increase much.…”
Section: Organ-wise Comparison Of Sod (Graph 7 -11)supporting
confidence: 88%